Early Childhood Teachers’ Professional Learning and Development during the Homeschooling Period - Barabási, Tünde; Stark, Gabriella-Mária (Technium Social Sciences Journal, 2022)
The interpretation framework of our study is the professional development and learning: Postholm’s definition of professional development, informal learning, the continuously professional learning defined by Szivák et al., mutual and cooperative learning. The central question of our empirical investigation was to what extent the practice of homeschooling during the pandemic can be framed as professional learning and development in the case of Hungarian early childhood teachers from Romania. We hypothesized that, despite the serious challenges of the pandemic, both practicing early childhood teachers and educational experts perceive and identify the elements of homeschooling which can also be framed as professional development and learning. The paper outlines the results of our empirical survey based on questionnaires and interviews. Our sample consisted of 403 early childhood teachers and 14 minority education experts resulting from convenience sampling. The investigation confirms that the picture of the continuously learning professional as an expectation of the teaching career is valid for (most) early childhood teachers. We found that the largest proportion of early childhood teachers proved in this period that they are open to new experiences and are capable of renewing procedural knowledge. In this period, professional learning received greater emphasis.